Amstal expression patterns in the Qur'an and Hadith and their application in Arabic learning - Oman Karya Suhada; Jimatul Arrobi (IJAS: Indonesian Journal of Arabic Studies, 2022)
Abstract : This study discusses the pattern of the expression "amstal" in the Qur'an and Hadith. The purpose of this study is to find out the pattern of the expression "amstal" in the Qur'an and Hadith, the characteristics, and aspects of the similarities between the two and its application in learning Arabic. This research method is descriptive analysis. The conclusion of this study is that the pattern of the phrase "amstal" in the Qur'an consists of patterns 1). ضرب الله مثلا كذا وكذا هل يستويان؟ ). ضرب الله مثلا لكذا كذا3 ). مثل كذا كمثل كذا4). مثل كذا ككذا.5). إنّ مثل كذا كمثل كذا،.(6 ). كذا كمثل كذا7. مثل كذا... while the expression pattern in the hadith consists of ( 1). مثل كذا مثل، 2). مثل كذا كمثل كذا، 3). مثل كذا ككذا، 4 كذا كما كذا، ,  (5). مثل كذا ومثل كذا كمثل كذا، 6). إنّ مثل كذا كمثل كذا، 7). مثل كذا ومثل كذا. The characteristics of the expression patterns in the Qur'an are “ ضرب الله مثلا كذا وكذا” and in hadith are “مثل كذا ومثل “ and the point of equality of the two is “مثل كذا ككذا” As for its application in learning Arabic through the practice of language patterns in the text of the Qur'an and hadith in the form of amstal expression patterns that allow students to develop the uslub into several examples such as.